Physiological Responses of Jatropha to Drought Stress in Coastal Sandy Land Conditions - Parwata, I Gusti Made Arya; Indradewa, Didik; Yudono, Prapto; Kusmarwiyah, Rukmini (UI Scholars Hub, 2012)
Jatropha curcas L., an important tropical biofuel crop, is reputed for its drought resistance, however, its ability to perform in dry conditions has still hardly been investigated. Changes in leaf water status, chlorophyll content, leaf surface temperature, stomatal conductance, proline and abcisic acid (ABA) content, transpiration and photosynthetic rate were studied in four Jatropha genotypes (IP-1A, IP-2M, Local superior and Yellow leaf) and subjected to drought stress in coastal sandy land conditions in Central Java, Indonesia. Drought stress significantly decreased the leaf water status, leaf chlorophyll content, stomatal conductance, transpiration and photosynthetic rate, and increased leaf temperature, proline and ABA content. Resistant genotypes (IP-1A and IP-2M) had significantly higher leaf water status, chlorophyll content and photosynthetic rate than susceptible genotypes (Local superior and Yellow leaf). There were no differences between the Jatropha genotypes on leaf temperature, stomatal conductance and transpiration rate